Oral History and the Canadian Labour Movement - Abella, Irving (Archivaria, 1977)
To the historian, oral history is a useful tool; to the labour historian it is an essential one. Unlike his colleagues in political, diplomatic and business history, the historian of the labour movement has few written documents on which to rely. Few of the important decisions and events in the' history of the trade union movement in Canada were ever recorded in print, and those that were, soon were discarded: memories of those decisions and events remain the private preserve of the men and women who were integrally involved. Only the oral historian can unearth many of these recollections; only oral history can fill many of the gaps in the history of the Canadian labour movement. --Introduction

Index — volume 32 — 1977 (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Liste des appréciateurs 1977 (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Portrait of a Jewish Professional Revolutionary: The Recollections of Joshua Gershman - Abella, Irving M. (Labour / Le Travail, 1977)
Provides an introduction to an autobiographical account of the life of Joshua Gershman, a Jewish Communist (1903-1988). Follows his life and the development of his ideals, and discusses his thoughts on various events. Discusses the connections between Jewish labour and socialism. Examines the conflicts between Jewish labour and Communism. Discusses tensions within Communism. Gershman resigned from the Communist Party of Canada in October 1977.

Collective Bargaining by Salaried Professionals - Adams, Georges W. (Relations industrielles / Industrial Relations, 1977)
This paper examines whether the traditional approach to collective bargaining fit s the needs of the salaried professionals or if special treatment is necessary.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Work of the Trade Union Field Officer - Adams, Roy J. (Relations industrielles / Industrial Relations, 1977)
This exploratory survey aims at presenting some of the characteristics of full-time union field officers.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Union Convention: An Examination of Limitations on Democratic Decision Making - Anderson, John C. (Relations industrielles / Industrial Relations, 1977)
This article examine a series of factors which may limit the existence of democratic decision making within the union convention.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Collective Bargaining in the Public Services of Canada - Anderson, John c.; Kochan, Thomas A. (Relations industrielles / Industrial Relations, 1977)
This paper examines the existing System of collective bargaining in the Public Service of Canada and the legislative suggestions of the Parliamentary Committee on Employer-employee Relations in the Public Service in light of the results of two major empirical investigations of collective bargaining in the federal public service of Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

OCDE, L’insertion des jeunes dans la vie active - Auger, Jean-Pierre (Relations industrielles / Industrial Relations, 1977)
This article reviews the general report "L’insertion des jeunes dans la vie active" by OCDE (Paris).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

A Study in Social Control: The Life of the Silver Miner in Northern Ontario - Baldwin, Douglas O. (Labour / Le Travail, 1977)
Examines the working conditions and employer-employee relationship in the mining camps of Cobalt, Ontario, following the discovery of silver in 1903. Discusses how the mine developed and the differences in lifestyle between the miners and the mine owners. Examines the miners’ working conditions and the actions that mine owners took in order to keep unions out.

Factors Related to Performance Variation Among Logging-Machine Operators - Barth, Richard T.; Cottell, Philip L. (Relations industrielles / Industrial Relations, 1977)
Despite the economic importance of large variations in individual productivity of logging-machine operators, few studies have attempted to examine the source of such variations. Based on data obtained for a total of 757 shifts of tree-felling activity, this exploratory study attempted to: (a) document variation in on-the-job performance and assign the variation to sources « within individual operators », « between operators », or « between firms »; (b) relate ob-served performance measured operator characteristics (ability and motivation); and (c) suggest ways in which average levels of job performance could be improved.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Indexation - Beach, Earl Francis (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Conseil économique du Canada, Horizon 1982 - Bélanger, Gérard (Relations industrielles / Industrial Relations, 1977)
This article reviews the special issue "Horizon 1982" by the Conseil économique du Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Vivre ensemble, une étude des disparités régionales - Bélanger, Gérard (Relations industrielles / Industrial Relations, 1977)
This article reviews "Vivre ensemble, une étude des disparités régionales" by the Conseil économique du Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Behavioral Issues in Management: The Canadian Context - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1977)
This article reviews "Behavioral Issues in Management: The Canadian Context" by H.C. Jain et R.N. Kanungo.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Managing Human Resources - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1977)
This article reviews "Managing Human Resources" by Leonard R. Sayles and George Strauss.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Personnal Management. A Human Resource System Approach - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1977)
This article reviews "Personnel Management. A Human Resource System Approach" by Elmer H. Burack and Robert D. Smith.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Personnel Management in Action: Skill Building Experiences - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1977)
This article reviews "Personnel Management in Action: Skill Building Experiences" by Arthur A. Whatley and Nelson L. Kelly.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Analyse coûts-bénéfices de fermetures d’entreprises - Belzile, Bertrand (Relations industrielles / Industrial Relations, 1977)
This article reviews "Analyse coûts-bénéfices de fermetures d’entreprises" by Jean-Aimé Guertin, Jean-François Guilloteau and Paul-Martel Roy.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Report on Social Security for Canada 1943 - Belzile, Bertrand (Relations industrielles / Industrial Relations, 1977)
This article reviews "Report on Social Security for Canada 1943" by Léonard Marsh.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’évaluation du rendement : perceptions de l’employé, de son supérieur et de ses collègues - Bergeron, Jean-Louis (Relations industrielles / Industrial Relations, 1977)
Le but de cet article est d'étudier la relation qui existe entre l’évaluation qu'un subalterne fait de son propre rendement et les évaluations qu'il reçoit de son supérieur et de ses collègues. Suite à une revue de la littérature, l'auteur présente et explique les résultats d'une recherche effectuée récemment auprès de 215 cadres d'une entreprise canadienne.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Détermination des salaires dans la fonction publique fédérale américaine : applicabilité au Québec - Bessette, Luc (Relations industrielles / Industrial Relations, 1977)
Cet article cherche à cerner des relations du travail dans les secteurs public et parapublic, à tracer un parallèle avec le système québécois et à y voir les possibilités d'application.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Compulsory Arbitration - Blouin, Rodrigue (Relations industrielles / Industrial Relations, 1977)
This article reviews "Compulsory Arbitration" by J. Joseph Lowenberg, Walter J. Gershenfeld, H.J. Glasbeek, B.A. Hepple, and Kenneth F. Walker.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Congédiement pour activité syndicale et autorisation préalable de congédier - Blouin, Rodrigue (Relations industrielles / Industrial Relations, 1977)
Dans cet article, l'auteur procède à une étude des règles juridiques qui précisent la protection dont bénéficie le salarié congédié à cause de l'exercice d'un droit qui lui résulte du Code du travail. Cette analyse est l'occasion d'identifier certaines failles et de proposer quelques modifications ; l'auteur s'interroge plus particulièrement sur l’opportunité d'assujettir ce congédiement à la technique de l'autorisation préalable avant de congédier.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Human Constraint, The Coming Shortage of Managerial Talent - Camire, André (Relations industrielles / Industrial Relations, 1977)
This article reviews "The Human Constraint, The Coming Shortage of Managerial Talent" by John B. Miner.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

An Analysis of Annual Turnover Rates for Canadian Union Presidents - Chaison, Gary N.; Rose, Joseph B. (Relations industrielles / Industrial Relations, 1977)
This paper re-examines the common views that presidential turnover occurs infrequently, is often the result of political forces and provides an adequate measure of union democracy. Moreover, the authors try to determine to what extent environmental factors influence annual presidential turnover rates among Canadian national unions.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Strikes as Safety-Valve Institutions - Chermesh, Ran (Relations industrielles / Industrial Relations, 1977)
The present study argues for the usefulness of searching for factors outside of the sub-system of industrial relations as partial causes of stike activity. It treats the industrial relations sub-system as an internal part of the overall social System, in which strikes are regarded as expressions of generalized social tension, i.e., as safety-valve institutions.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’effet de la grève sur le contrat individuel de travail : l’affaire McGavin Toastmaster - D’Aoust, Claude (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Bibliography of Industrial Relations in the Railroad Industry - Dion, Gérard (Relations industrielles / Industrial Relations, 1977)
This article reviews "Bibliography of Industrial Relations in the Railroad Industry" by James O. Morris.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Collective Bargaining and Public Benefit Conferral: A Jurisprudential Critique - Dion, Gérard (Relations industrielles / Industrial Relations, 1977)
This article reviews "Collective Bargaining and Public Benefit Conferral: A Jurisprudential Critique" by Robert S. Summers.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Guide to Statutory Provisions in Public Sector Bargaining – Impasse Resolutions Procedures - Dion, Gérard (Relations industrielles / Industrial Relations, 1977)
This article reviews "Guide to Statutory Provisions in Public Sector Bargaining – Impasse Resolutions Procedures" by Helen S. Tanimoto.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Current Industrial Relations Scene in Canada 1977 - Dion, Gérard (Relations industrielles / Industrial Relations, 1977)
This article reviews "The Current Industrial Relations Scene in Canada 1977" edited by H.D. Wood and Pradeep Kumar.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Déontologie - Dussault, Gilles (Relations industrielles / Industrial Relations, 1977)
This article reviews the report "Déontologie" by the Groupe consultatif de déontologie.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Health Economics Symposium: Proceedings of the First Canadian Conference - Dussault, Gilles (Relations industrielles / Industrial Relations, 1977)
This article reviews "Health Economics Symposium: Proceedings of the First Canadian Conference" by R.D. Fraser.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La sociologie et les Sciences de la Société - Dussault, Gilles (Relations industrielles / Industrial Relations, 1977)
This article reviews "La sociologie et les Sciences de la Société" created under the direction of Jean Cazeneuve.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Development of an African Working Class - Dussault, Gilles (Relations industrielles / Industrial Relations, 1977)
This article reviews "The Development of an African Working Class" by R. Sandbrook and R. Cohen.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Final Position Arbitration and Intertemporal Compromise - Dworkin, James B. (Relations industrielles / Industrial Relations, 1977)
This paper seeks to present further evidence from the realm of professional baseball in regard to Swimmer's criticism of final offer procedure.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Mobility Potential and the Quality of Life in Working-Class Lowell, Massachusetts: The French Canadians ca. 1870 - Early, Frances H. (Labour / Le Travail, 1977)
Discusses the quality of life amongst French-Canadians living in Lowell, Massachusetts in 1870. Explores the development of a working-class community in the mill town after the American Civil War, in particular the migration of French-Canadians into the community. Analyzes the occupations of the French-Canadian immigrants, concluding that the vast majority were working-class with low mobility potential. Examines the living conditions of working-class people at the time. Argues that life was difficult for French-Canadian immigrants in New England during this period.

The Decline of the Sailor as a Ship Labourer in 19th Century Timber Ports - Fingard, Judith (Labour / Le Travail, 1977)
Examines the role that sailors played in moving cargo in Canadian timber ports of the nineteenth century. Discusses the behaviour of sailors during the period, specifically desertion. Analyzes the tension between sailors and ship labourers' unions due to competition for work. Concludes that the tension was ended by technological advances, notably the invention of the steamship.

Un modèle d’offre de travail des familles à faible revenu au Québec - Fortin, Bernard; Belzile, Bertrand (Relations industrielles / Industrial Relations, 1977)
L'objet de cet article est de présenter de façon synthétique quelques aspects méthodologiques d'une recherche entreprise sur le comportement de travail des parents de familles québécoises à faible revenu.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le travail de la femme au Québec : l’évolution de 1940 à 1970 - Gosselin, Hélène (Relations industrielles / Industrial Relations, 1977)
This article reviews "Le travail de la femme au Québec : l’évolution de 1940 à 1970" by Francine Barry.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Through the Prism of the Strike: Industrial Conflict in Southern Ontario, 1901–14 [excerpts] - Heron, Craig; Palmer, Bryan D. (Canadian Historical Review, 1977)
...To go beyond such generalized condemnation and probe deeper into the contours and context of industrial strife, we have examined strike activity between 1901 and 1914 in ten southern Ontario cities that were emerging as major industrial centres. ...Through an examination of this conflict, in which the strike looms large, we can learn much more about class relationships in these early years of a maturing central Canadian capitalism.

The Estimate of Productivity Growth in Canada’s Prices and Incomes Policy - Ingerman, Sidney H.; Rose-Lizée, Ruth (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Employee Pay and Benefit Preferences at Canadian National: New Evidence - Jain, Harish C. (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Comparative Manpower Strategies - Jenness, R. A. (Relations industrielles / Industrial Relations, 1977)
The author presents a comparison of how different member countries of the OECD have developed their man-power strategies over the past decade in light of the unique institutional and cultural circumstances.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Christian Trade Unionism in France: A Left Socialist Experience - Kassalow, E. M. (Relations industrielles / Industrial Relations, 1977)
The author presents a synthesis of the evolution of the Confédération française démocratique du travail. The French Democratic Confederation of Labor.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le développement des ressources humaines, fonction négligée par l’entreprise - Larouche, Viateur (Relations industrielles / Industrial Relations, 1977)
L'auteur, après avoir présenté les principaux partenaires de la formation dans le milieu organisationnel, situe le développement des ressources humaines dans le contexte de la gestion des ressources humaines. Dans un second temps, certaines caractéristiques des activités de formation dans le milieu organisationnel sont explicitées. Finalement, à l'aide de statistiques, l'auteur analyse la situation qui prévaut dans les entreprises québécoises.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les Travailleuses Montréalaises entre les deux guerres - Lavigne, Marie; Stoddart, Jennifer (Labour / Le Travail, 1977)
Discusses female workers in Quebec during the period between the two World Wars, 1919-1939. Analyzes the unique aspects of female labour in Quebec. Examines the living and working conditions and ideologies of femininity during this particular period. Concludes that the connection between waged work and the achievement of civil rights is a complex and indirect one. Argues that it is necessary to stop investigating women as a homogenous group, instead taking into account the differences between women.

The Worker and the Job - Lemelin, Maurice (Relations industrielles / Industrial Relations, 1977)
This article reviews "The Worker and the Job" by The American Assembly, edited by Jerome M. Rosow.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Economic Returns on Under-Graduate Fields of Study in Canadian Universities, 1961 to 1972 - Mehmet, Ozay (Relations industrielles / Industrial Relations, 1977)
This paper provides comparable estimates of private rates of return on a set of21 undergraduate courses of study at Canadian Universities in 1961, 1969 and 1972, and then attempts to explain observed shifts in the college labour market using a simple multiple regression model.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Salaire minimum ou quand le diable se fait moine - Migué, Jean-Luc (Relations industrielles / Industrial Relations, 1977)
L'auteur cherche à savoir pourquoi, malgré leur inefficacité reconnue, des lois du salaire minimum continuent à être adoptées par les législateurs.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Absenteeism and Overtime: Double Jeopardy - Mikalachki, Al; Chapple, D. C. (Relations industrielles / Industrial Relations, 1977)
This study investigated factors leading to absenteeism in a large auto plant employing about 1,000 workers. The hypotheses examined dealt with the effect on absenteeism of: the skill required for the job, the worker's age and health, and the base pay rate. The initial analysis proved opposite of what is usually found. An additional factor was examined: the ability of the worker to control the amount of overtime he worked. The data then showed that the worker who is able to achieve a set income for the fewest days in attendance by working overtime, uses this device to spend less time on the job. Ideas were also presented to show that positive reinforcement of good attendance can result in decreased absenteeism.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le contrôle et le décontrôle des prix et des revenus : un commentaire - Montmarquette, Claude (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Divergence ou convergence du mouvement syndical et du mouvement coopératif des Caisses Desjardins - Morin, Fernand (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’injonction en temps de grève - Morin, Fernand (Relations industrielles / Industrial Relations, 1977)
Dans cette étude, l'auteur a voulu connaître l’usage qui peut être fait de l’injonction comme moyen de contrôle de l'exercice du droit de grève à partir d'une analyse sommaire de 204 dossiers portant uniquement sur la procédure d'obtention et le contenu de la décision judiciaire.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Taking on the Grand Trunk: The Locomotive Engineers Strike of 1876-7 - Morton, Desmond (Labour / Le Travail, 1977)
Examines the Locomotive Engineers strike of 1876-77 against the Grand Trunk Railway of Canada, the reaction of the company and the government. Argues that the strike set an important precedent for successful job action. Concludes that the polarizing nature of strikes forces people and governments to choose sides in labour conflicts.

The Rationale for Government Involvement in Manpower Training in Canada: Theory and Evidence - Newton, Keith (Relations industrielles / Industrial Relations, 1977)
This paper intends to develop more fully the theoritical aspects of the « structural maladjustment » hypothesis and to examine the empirical evidence for Canada for substantiation of government intervention in the training field.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Influence of Public Opinion in Labour-Management Relations and Dispute Settlement - Peitchinis, Stephen G. (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Candide-Cofor et la prévision de besoins en main-d’oeuvre par occupation et par industrie au Canada - Proulx, Pierre-Paul; Bourgault, Luce; Manegre, Jean-François (Relations industrielles / Industrial Relations, 1977)
Cet article explique comment les modèles Candide et Cofor peuvent être utilisés conjointement pour effectuer, à l'échelle d'une province, des prévisions d'emploi par profession dans chaque industrie.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Psychological Conflict Models: Their Applicability to the Theory of Collective Bargaining - Reid, Frank (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Response of Wages to the Removal of Controls: The American Experience - Reid, Frank (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Paradox of Unemployment and Job Vacancies: Comment - Reid, Frank J. (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Construction Labour Relations Association in Canada - Rose, Joseph B. (Relations industrielles / Industrial Relations, 1977)
This paper examines the relatively recent movement by employers in the construction industry toward province-wide associations specializing in labour relations. Beginning with the formation of the Construction Labour Relations Association of British Columbia (CLRA) it reviews the influences of contractor cooperation, union opposition and labour laws on the ability of these organizations to bring unity to contractor ranks and alleviate what has been described as the imbalance of power in construction labour relations. There is also an examination of the organizational characteristics of these CLRA-type organizations which reveals how they have been able to maintain control of members and reduce fragmentation.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Cyclical Instability in Residential Construction in Canada - Rose, Joseph B. (Relations industrielles / Industrial Relations, 1977)
This article reviews "Cyclical Instability in Residential Construction in Canada" by Joseph H. Chung.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Un modèle de l’offre de travail des bénéficiaires de l’aide sociale au Québec - Rousseau, Henri-Paul (Relations industrielles / Industrial Relations, 1977)
Cet article présente la stratégie de recherche d'un projet qui vise à analyser le comportement des bénéficiaires de l'aide sociale concernant leurs activités de travail et de prospection d'emploi, afin de mieux connaître les déterminants de leurs plans d'offre de travail.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Cost-of-Living Adjustments in Union-Management Agreements - Saint-Laurent, Jacques (Relations industrielles / Industrial Relations, 1977)
This article reviews "Cost-of-Living Adjustments in Union-Management Agreements" by Robert H. Ferguson.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Equal Pay of Equal Value, A Discussion Paper - Saint-Laurent, Jacques (Relations industrielles / Industrial Relations, 1977)
This article reviews "Equal Pay of Equal Value, A Discussion Paper" by the Ontario Ministry of Labour.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Evaluating the Labor-Market Effects of Social Programs - Saint-Laurent, Jacques (Relations industrielles / Industrial Relations, 1977)
This article reviews "Evaluating the Labor-Market Effects of Social Programs" edited by O. Ashenfelter and J. Blum.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Wage Price Controls and Labor Market Distortions - Saint-Laurent, Jacques (Relations industrielles / Industrial Relations, 1977)
This article reviews "Wage Price Controls and Labor Market Distortions" by Daniel J.B. Mitchell and Ross E. Azevedo.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les horaires variables - Savoie, André (Relations industrielles / Industrial Relations, 1977)
This article reviews "Les horaires variables : examen de la littérature" by B. Turgeon, "L’horaire variable au Québec : rapport d’enquête" by Louise H. Côté and Normande Lewis, "L’horaire variable : rapport de la mission d’étude en Allemagne et en Suisse" by B.M. Tessier and B. Turgeon, and "Les répercussions de l’horaire variable sur l’individu" by R. Boulard, Louise H. Côté, S. Guimond and B. Turgeon.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

A Profusion of Issues: Immigrant Labour, the World War, and the Cominco Strike of 1917 - Scott, Stanley (Labour / Le Travail, 1977)
Examines labour relations at the Consolidated Mining and Smelting Company smelter in Trail, British Columbia, that resulted in unionization in 1916. Analyzes the issues that had prevented unionization earlier, including opposition from immigrants and the First World War. Discusses the events which led up to the 1917 strike, that lasted until 20 December 1917.

Labour Arbitration and the Refusal to Perform Hazardous Work - Sentes, Ray (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Paradox of Unemployment and Job Vacancies: Reply - Skolnik, Michael L.; Siddiqui, Farid (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Holmes Foundry Strike of March 1937: We'll Give Their Jobs to White Men! - Snow, Duart (Ontario History, 1977)
Examines the 1937 sit-down strike at the Holmes Foundry in Sarnia, Ontario, during which the strikers were beaten and . Discusses the impetus for the strike as well as the situation in the area and the foundry in particular. Comments on the strategy of the strikers and the stoking of racial hatred by the management and local authorities. The author argues that the Holmes Foundry strike illustrated the exent to which the elite was willing to go to crush the strike.
Keywords: Race; Strikes; Work

Bullock and the Aftermath - Sturmthal, Adolf (Relations industrielles / Industrial Relations, 1977)
This study presents the main recommendations of Lord Bullock's Committee of Inquiry on Industrial Democracy in Great Britain.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Impact of the Two Dispute Resolution Processes in Negotiations - Subbarao, A. V. (Relations industrielles / Industrial Relations, 1977)
This paper attemps to answer the questions as to why the federal public servants alther their options from the arbitration process to the conciliation process.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Wage Differentials Between Native and Foreign Born Canadians - Tandon, B. B.; Tandon, K. K. (Relations industrielles / Industrial Relations, 1977)
The intent of this paper is to estimate the extent of male-female wage differential in a local labor market among the Native born and Foreign born Canadians
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Critères d’augmentations de salaires chez les cadres canadiens-français, canadiens-anglais et américains - Thériault, Roland D.; Dyer, Lee D. (Relations industrielles / Industrial Relations, 1977)
Cette étude a pour but de répondre aux questions suivantes: premièrement, est-ce qu'il existe des différences significatives selon les cadres dans les critères utilisés pour déterminer leurs augmentations de salaire et ceux qu'ils désirent? Deuxièmement, est-ce qu'il existe des différences entre les critères utilisés et ceux désirés par les cadres appartenant à des milieux culturels différents? En dernier lieu, quelles caractéristiques pourraient expliquer l'importance relative qu'ils accordent aux critères désirés dans la détermination des augmentations de salaire ?
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Collective Bargaining in the Essential and Public Service Sectors - Thompson, Mark (Relations industrielles / Industrial Relations, 1977)
This article reviews "Collective Bargaining in the Essential and Public Service Sectors" by Morley Gunderson.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

"The Large and Generous View:" The Debate on Labour Affiliation in the Canadian Civil Service, 1918-1928 - Thomson, Anthony (Labour / Le Travail, 1977)
Examines the connection between middle-class civil servants and trade union ideologies during the 1918-28 period. Discusses the growing militancy of public sector employees after the First World War. Analyzes the tensions between white-collar workers and manual labourers, and white-collar workers' connections to the labour movement. Discusses the implications of the situation of middle-class workers with regards to the class struggle and proletarianization. Concludes that proletarianization is not an either/or process, and that there are opportunities for alliances between salaried workers and the proletariat. The text is a revised version of a paper originally presented at the Annual Meeting of the Committee on Socialist Studies in Fredericton, New Brunswick, on June 11-12, 1977.

“Women in Between”: Indian Women in Fur Trade Society in Western Canada - Van Kirk, Sylvia (Historical Papers, 1977)

La consultation : un processus andragogique centré sur le client - Wallot, Hubert (Relations industrielles / Industrial Relations, 1977)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Towards « Participative » Multinationals - Warner, Malcolm; Peccei, Riccardo (Relations industrielles / Industrial Relations, 1977)
If the labour movement is strong, this may not only simultaneously make for more effective participation at the National plant levels, but also via pressure on the State, to very much limit the role of the multi-national corporations.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Participation et négociation collective - Weiss, Dimitri (Relations industrielles / Industrial Relations, 1977)
This article reviews "Participation et négociation collective" by Laurent Bélanger, Jean Boivin and Gilles Dussault, under the direction of Alain Laroque.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Liberal Corporatist Ideas of Mackenzie King - Whitaker, Reginald (Labour / Le Travail, 1977)
Examines the life of William Lyon Mackenzie King, specifically the development of his ideas around class and democracy. Traces King's life from childhood to his election as prime minister in 1921. Discusses how various events in King's life contributed to his liberal corporatist ideas. Argues that King's ideas about corporatism were ahead of his time.